Design and Implementation of Intravenous Infusion Monitoring System Based on Wireless Sensor Network with Smartphone Display - Teguh, Teguh Afrianda; yulkifli, Yulkifli (Journal of Experimental and Applied Physics, 2024)
This research introduces a Wireless Sensor Network (WSN) based infusion monitoring system utilizing Internet of Things (IoT) technology. Infusion management is critical in healthcare, but manual supervision often lacks accuracy and control. Through the use of optocoupler and load cell sensors, this system enables automated calculation of the infusion drop rate per minute and evaluation of the remaining fluid percentage. In this study, tests were conducted using optocoupler sensors to calculate the drop rate per minute and load cell sensors to measure the remaining fluid percentage. Measurement results are monitored via smartphone, allowing healthcare professionals easy and rapid access to data. Furthermore, the innovation of this system lies in the application of Internet of Things (IoT) technology, enabling remote control through Wireless Sensor Network (WSN). Thus, one nurse can oversee multiple infusions using just one smartphone. The testing results demonstrate a high level of accuracy, with an average precision rate of 97% for drop rate measurements and 93% for the remaining fluid percentage measurements. This system offers an efficient and controlled solution for infusion fluid management, ensuring optimal healthcare services for patients. By integrating IoT and WSN technologies, this research paves the way for the development of more advanced and connected infusion monitoring systems, supporting enhanced patient care in the era of globalized healthcare.